Exploring the surveillance technology discourse: a bibliometric analysis and topic modeling approach - Karlsson, Kalle; Dalipi, Fisnik (Frontiers in Artificial Intelligence, 2024)
Prevention of crime represents a difficult endeavor that has legal, political, and cultural implications. Surveillance technologies are seen as a facilitator that may help law enforcement and other relevant parties in that mission. Drones, cameras, and wiretaps are a few instances of these devices. The increasing use of these devices necessitates addressing related challenges pertaining to many stakeholders and their cultural, political, and legal aspects. Therefore, the objective of this study is to analyse the impact of surveillance technologies and identify commonalities and differences in perspectives among social media users, and researchers. Extraction of data from platform X (previously known as Twitter) and Scopus was performed, resulting in the retrieval of 88,989 tweets and 4,874 research papers. The tweets and research papers were subjected to analysis with topic modelling, an unsupervised machine learning approach. The study revealed the presence of seven distinct topics within the Scopus dataset, whereas the X/Twitter dataset exhibited four distinct topics. The analysis revealed that privacy received little attention across the datasets, indicating its relatively low prominence. The military applications and their usage have been documented in academic research articles as well as tweets. Based on the empirical evidence, it seems that contemporary surveillance technology may be accurately described as possessing a bi-directional nature, including both sousveillance and surveillance, which aligns with Deleuzian ideas on the Panopticon. The study's findings also indicate that there was a greater level of interest in actual applications of surveillance technologies as opposed to more abstract concepts like ethics and privacy.